Key Concepts in the Study of Religions in Contact - Stünkel, Knut Martin, (Dynamics in the History of Religions ;, 2025)
There is no religion lest there are two religions. Therefore, it is only possible to examine the history of religions by taking the crucial situations of contact into account. Contact needs concepts. Not only scholars but also participants in situations of contact are forced to conceptualize themselves and the other. Taking its point of departure from the contact-based approach to the study of religion, the present volume examines and reassesses a selection of concepts and models (attraction, dynamics and stability, tradition, transcendence/immanence, senses, secret, space) used to come to terms with the phenomenon of contact as the dynamizing element of the history of religions.